PERAN GURU PPKN DALAM MEMBENTUK KARAKTER DISIPLIN SISWA DI SMA NEGERI 2 BELIMBING - Juri Juri; Sapto Purnomo; Franciska Regina Beeta (JURNAL PEKAN : Jurnal Pendidikan Kewarganegaraan, 2023)
This research aims to analyze the rore of Pancasila and Citizenship Education teachers in forming disciplinary characters, especialy in the SMA Negeri 2 Belimbing. This is because discipline is an important factor that supports students success during their education in everyday life in society. Without good discipline, it is certain that students will experience various obstacles, where this obstacles are, most likely not be able to be overcome. If so, the person concerned will surrender to the situation. However, to form a disciplined character is certainly not an easy matter, because it is influenced by at least two factors, namely internal and exsternal. Internal factors relate to the students themselves, namely to extent to which the are committed to progressing and developing the talents that exist within themselves. Meanwhile, exsternal factors, include family, friends, community, government, and the teachers at school. The method used in this research is descriptive qualitative. Data was collected using observation, interviews and documentation studies. Meanwhile, the data processing refer to Mile and Huberman’s theory. The results of this reseach show that teachers, especially Pancasila and Citizenship Education teacher have quite an important role in shaping students disciplinary character. There are several strategies used, including pioneering the establishment of an honesty kantin, coming to school on fixed time, entering and leaving class according to a predetermined schedule, looking nead, implementing school regulations properly and correctly and colaborating with other teachers.  Keywords: Teacher Role, Student Discipline Character, Pancasila and Citizenship Education